PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 008 TELUK MEGA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Zaini Zaini; Munjiatun Munjiatun; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study in the background backs by low yields social studies class student V SDN 008 Teluk Mega bay with an average grade 67.4%. While the value of minimum criteria for completeness (KKM) IPS is 70. Among the students numbering 25 people, only 10 students who reach KKM with classical completeness 40%)%. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes IPS fifth grade students of SDN 008 Mega bay with the Application Model of Quantum Teaching To Improve Student Learning Outcomes IPS Class V SDN 008 Mega Gulf